Sustainability assessment of coupled human and natural systems from the perspective of the supply and demand of ecosystem services - Liu, Haimeng; Xing, Lu; Wang, Chengxin; Zhang, Haiyan (Frontiers in Earth Science, 2022)
The sustainability of coupled human and natural systems (CHANS), linked to several of the United Nation’s Sustainable Development Goals, affects both global sustainable development and human wellbeing. However, few studies have explored the relationship between the whole human system and the natural system from the perspective of supply and demand. Based on ecosystem service concept and Maslow’s hierarchy of needs, we constructed an ecosystem services supply index (ESSI) and a human demand index (HMDI) and then analyzed the spatial mismatch of the ESSI and HMDI in 338 prefecture cities in China. We propose a supply-demand balance index inspired by the doughnut theory and demonstrate the conflicts and synergies between ecosystems and human systems. Our results show that the ESSI decreased from 2000 to 2010, but remained almost unchanged from 2010 to 2020. The low ESSI values were mainly distributed over the North China Plain, the Yangtze River Delta, and the Sichuan Basin. The HMDI increased from 2000 to 2020, but the rate of increase has slowed since 2010. The high HMDI values were mainly distributed over the east coast of China, Inner Mongolia, and part of Xinjiang province. From 2000 to 2020, the cities with spatial mismatches of the ESSI and HMDI showed a significant increase and spatial agglomeration. The sustainability of most regions showed a decreasing trend, and the higher the value of the supply-demand balance index, the faster the speed of decrease. Overall, there were more regions in a state of conflict between the natural ecosystem and humans than in a synergistic state, although this number has decreased since 2010. Urban agglomerations and western regions should receive more attention for their ecological health. This study provides a new methodology to assess the sustainability of CHANS that could be applied to other locations. Our findings could support the Chinese government in regional ecosystem governance and territorial space planning.